EFEKTIVITAS DAN MANFAAT PENERAPAN LITERASI BERBASIS BUDAYA LOKAL PADA ANAK SEKOLAH DASAR - Hairi Habibullah; Haifaturrahmah; Syafruddin Muhdar; Sukron Fujiaturrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of culture-based literacy in elementary school students is an essential strategy to improve the quality of learning while instilling local wisdom values from an early age. Literacy is not only understood as the ability to read and write but also includes skills in understanding, interpreting, and connecting information with everyday life contexts. By integrating local culture into literacy learning, children can more easily comprehend the material because it relates to their daily experiences. In addition, culture-based literacy fosters a sense of pride, identity, and appreciation for the traditions they inherit. The effectiveness of this approach is reflected in the increased reading interest, critical thinking skills, and creativity of students in expressing ideas. Other benefits include creating a fun, interactive, and socially relevant learning environment. The implementation of this program also supports cultural preservation while equipping children with adaptive literacy skills in line with the demands of the modern era. Thus, culture-based literacy can serve as a strong foundation for building a generation that is intelligent, has strong character, and remains rooted in the cultural values of the nation